Development of Matific-Assisted Mathematics E-Modules to Increase Elementary School Students' Learning Interest - Putri Melinda Rahmawati; Ananda Nadhifah Yustikarinda; Dita Apriselia Ratna Shinta; Ummu Sholihah; Eni Setyowati (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
This study aims to develop a Matific-assisted mathematics e-module to increase elementary school students' learning interest in plane geometry. The method used is research and development (R&D) with the ADDIE model. The resulting e-module product was validated by material experts and media experts to determine the level of validity, then tested through implementation to determine the practicality and effectiveness of the product on fourth-grade students at SDIT Al-Azhar Kediri. The results of the study indicate that the Matific-assisted mathematics e-module is valid, practical, and effective to be used to increase elementary school students' learning interest. The results of the material expert validation show a percentage of 80% in the